THE INFLUENCE OF PRODUCT, SERVICE QUALITY AND PROMOTION ON THE CUSTOMER'S DECISION TO TAKE CREDIT (Case Study PT. Pegadaian Lamongan) - Eka Rizky Romadloni; Zulkifli Lubis; Danu Kusbndono (Sean Institute, 2022)
This research aims to determine the influence of product, service quality, and promotion on the customer’s decision to take credit in PT. Pegadaian Lamongan. Sampling techniques usd are purposive sampling. So it can be know that only Promotion variable (X3) has a partial impact on Y variable. And simultaneous test has been peformed and the resulting value of F hitung (3,775) bigger than F table (2,71), the variable product, service quality, and promotion together would have a significant impact on the customer’s decision to take credit.